Regional industrial development in a dual-core industry space in China: The role of the missing service. (December 2019) - Hu, Chaoran; Zhou, Yi; He, Canfei
Abstract: Developing competitive industries is important to regional growth. Existing studies have emphasized that regions are more likely to succeed if they develop new industries based on their existing industrial structure or local competences. However, to measure a region's industry structure, earlier literature uses only the network of relatedness between manufacturing industries, while largely overlooking industries in the service sector. Based on a detailed industry-region level dataset from China's National Economic Census in 2008 and 2013, we extend Hidalgo's method and provide robust evidence that industrial structure of China is shaped by both service and manufacturing industries. By including service industries, we reveal that China's industry space has two densely connected cores. Manufacturing and service industries are closely related, and both are important to regional industrial development. Contrary to the conventional wisdom, undeveloped regions are found to locate in one of the connected cores, thus both developed and undeveloped regions are suggested to develop smartly based on their existing competences. Findings of our work cast doubts on some current path-breaking policies for undeveloped regions to develop upscale but unrelated industries.